A DESCRIPTIVE COMPARISON OF RESPONSE OF ORAL HYPOGLYCEMIC AGENTS AMONG T2DM IN A BACKDROP OF INSULIN RESISTANCE - Sandip Chakraborty; Amrita Karmakar; Indranil Dawn; Sangita Samadder; Dipa Mondal (The Indonesian Journal of Public Health, 2023)
Introduction:Different homeostatic models for the assessment of beta cell function in patients with insulin resistance in type 2 diabetes mellitus suggest that Dipeptidyl Peptidase (DPP-4) inhibitors cause less beta cell stress. Aims: The present study aimed to compare and contrast insulin resistance in two groups of patients taking oral hypoglycemic agents, DPP-4 plus metformin and glimepiride plus metformin, on the basis of fasting and postprandial c-peptide and insulin resistance estimated by homeostatic model assessment of insulin resistance (HOMA-IR). Methods: This preliminary descriptive observational study was conducted from 2018 to 2019 in the service Laboratory of the Department of Biochemistry, in collaboration with the Endocrinology Department, Nil Ratan Sircar Medical College and Hospital, Kolkata. Serum C-peptide, serum insulin, and plasma glucose levels were measured in both fasting and post-prandial states along with glycated hemoglobin. Result: In the fasting and fed state, the secretagogue effect of glimepiride-metformin combination was significantly higher (p = 0.017) than that of the linagliptin-metformin combination. Conclusion: Patients treated with glimepiride showed high post prandial insulin levels and high post prandial glucose excursion. This finding can be explained by the probable increase in insulin resistance, which is reflected in their post-prandial C peptide level. However, in the case of linagliptin, one mechanism of decreased post-prandial glucose is believed to be the inhibition of α-cell glucagon release, thereby relieving β-cell stress